Smoking, allergy, and the differential white blood cell count. Issue 1 (January 1985) - Taylor, R G; Gross, E; Joyce, H; Holland, F; Pride, N B
Abstract : Dutch workers have proposed that people with asthma and those smokers who develop chronic airflow obstruction share a common allergic constitution. To study whether smoking itself is associated with indicators of allergy, we have examined 237 men aged 51-61 years (120 smokers, 73 ex-smokers, and 44 non-smokers) who were recruited to a long term study of lung function in 1974, at which time men with a clinical diagnosis of asthma were excluded. Smokers, ex-smokers, and non-smokers did not differ in personal or family history of allergic disease, but the prevalence of positive responses to skinprick tests was greater in ex-smokers (59%) than in the other two groups (33% and 34%). In men with negative responses to skinprick tests total serum IgE was greater in smokers (log10 mean 1.41 IU/ml) and in ex-smokers (log10 mean 1.53 IU/ml) than in non-smokers (log10 mean 1.12 IU/ml). In men with positive skin test responses serum IgE was similar in the three groups (log10 mean ranging from 1.68 to 1.78 IU/ml). Geometric mean total white cell counts in the peripheral blood were higher in smokers (7.34 X 10(9)/l) than in non-smokers (5.82 X 10(9)/l); the value in ex-smokers (6.16 X 10(9)/l) was intermediate. Absolute blood eosinophil counts were increased in smokers disproportionately to the increase in total white cell count. Thus smoking is associated with small increases in some markers of allergy. These changes are probably acquired after the onset of smoking but sequential studies are required to amplify these cross sectional observations. Smokers whose skin test responses are positive appear more likely to give up smoking.